Metaflammasome components in the human brain: a role in dementia with Alzheimer's pathology?. (8th June 2016) - Taga, Mariko; Minett, Thais; Classey, John; Matthews, Fiona E.; Brayne, Carol; Ince, Paul G.; Nicoll, James AR; Hugon, Jacques; Boche, Delphine; ,
Abstract: Epidemiological and genetic studies have identified metabolic disorders and inflammation as risk factors for Alzheimer's disease (AD). Evidence in obesity and type‐2 diabetes suggests a role for a metabolic inflammasome ("metaflammasome") in mediating chronic inflammation in peripheral organs implicating IKKβ (inhibitor of nuclear factor kappa‐B kinase subunit beta), IRS1 (insulin receptor substrate 1), JNK (c‐jun N‐terminal kinase), and PKR (double‐stranded RNA protein kinase). We hypothesized that these proteins are expressed in the brain in response to metabolic risk factors in AD. Neocortex from 299 participants from the MRC Cognitive Function and Ageing Studies was analysed by immunohistochemistry for the expression of the phosphorylated (active) form of IKKβ [pSer 176/180 ], IRS1 [pS 312 ], JNK [pThr 183 /Tyr 185 ] and PKR [pT 451 ]. The data were analyzed to investigate whether the proteins were expressed together and in relation with metabolic disorders, dementia, Alzheimer's pathology and APOE genotype. We observed a change from a positive to a negative association between the proteins and hypertension according to the dementia status. Type‐2 diabetes was negatively related with the proteins among participants without dementia; whereas participants with dementia and AD pathology showed a positive association with JNK. A significant association between IKKβ and JNK in participants with dementia and AD pathology was observed, but not in those without dementia. Otherwise, weak to moderate associations were observed among the protein loads. The presence of dementia was significantly associated with JNK and negatively associated with IKKβ and IRS1. Cognitive scores showed a significant positive relationship with IKKβ and a negative with IRS1, JNK and PKR. The proteins were significantly associated with pathology in Alzheimer's participants with the relationship being inverse or not significant in participants without dementia. Expression of the proteins was not related to APOE genotype. These findings highlight a role for these proteins in AD pathophysiology but not necessarily as a complex.